Stagnating CO2 emissions with in-depth socioeconomic transition in Beijing. (15th October 2018) - Wang, Jie; Xiong, Yiling; Tian, Xin; Liu, Shangwei; Li, Jiashuo; Tanikawa, Hiroki
Highlights: The turning point of Beijing's production-based CO2 emissions arrived in 2007. CO2 emissions declined in industry due to its further transferring and transition. Upgradation of internal structure in services promoted the CO2 emissions peak. Consumption composition change in services reduced emissions with urbanization. Beijing's experience of peaking CO2 emissions guides other cities in developing countries. Abstract: Curbing the growth of global CO2 emissions and limiting global average temperature rise to well below 2 °C are important targets for the international society after the Paris Climate Change Conference. Given the continuously increasing emission trends in most of the developing world, peaking emissions as soon as possible during the developing and transition process is a key challenge in realizing the target globally. In this study, we established a comprehensive analysis framework for peaking stage analysis, based on three scopes accounting, and estimating the impact of in-depth socioeconomic transitions on peaking stages. We further applied it to Beijing, which reversed its growth trend in CO2 emissions and acted as a pioneer in fulfilling the peaking target of emissions during in-depth socioeconomic transition period, in recent years. We found that the turning point for production-based CO2 emissions in Beijing appeared around 2007, which stopped growing and has since been fluctuating around 100 Mt. During the in-depth industrialization process, accelerating the elimination of energy and carbon intensive industries, such as resource-related heavy manufacturing, promoting the transition from industries to services, and upgrading the internal structure of industries, were key factors determining the CO2 emissions peak in Beijing. Meanwhile, the optimization of the internal production structure of consumer and producer services also led to a declining trend of services with the in-depth industrial transition. During the in-depth urbanization process, the reduced CO2 intensity and optimized production structure of shelter and household equipment, and upgraded services dominated consumption structure were the main reasons for urban household CO2 mitigation. Clarifying the mechanism of the CO2 emissions peak during the in-depth socioeconomic transition period in Beijing will help us understand the challenges of peak better and provide valuable references for other countries and regions in the developing world that are facing peaking emissions challenges in the processes of their development.